2011 social media directory : the ultimate guide to Facebook, Twitter, and LinkedIn resources - Riley, Jeffery A. (Que, 2010)
Quick access to today's top Facebook, Twitter, and LinkedIn resources - on business, entertainment, politics, health, sports, and much more! A single, up-to-the-minute source for all the best new resources on today's top social networks More than 3,000 entries on parenting, shopping, fashion, sports, travel, religion, and many other topics A huge timesaver: helps users instantly uncover hidden "gems" they'd otherwise have to search for, stumble upon, or never find at all!